Permanent canine eruption into the grafted alveolar cleft region: are there predictor factors for impaction? - Holz, Isabella Simões (2017)
Background: Predictor factors for early diagnosis of maxillary canine impaction (Mx.CI) in unilateral complete cleft lip and palate (UCLP) have not yet been clearly described in the literature. Objectives: The aim of this study was to investigate the eruption pattern of maxillary permanent canines in the alveolar cleft area before and after the secondary alveolar bone grafting (SABG) and to assess the risk indicators for canine impaction and its association with other dental anomalies. Methods: The sample consisted of 75 patients with UCLP who underwent SABG with rhBMP-2 with a mean age of 9.8 years of age at a single center. The study design was a split mouth with the non-cleft hemi-arch comprising the control group. Panoramic radiographs taken before (T1), immediately after (T2) and one year after SABG (T3) were used to assess the following parameters in both cleft (CS) and non-cleft (NCS) sides: canine mesiodistal angulation, canine height relative to the occlusal plane and canine mesial displacement and superimposition with the neighboring maxillary incisors. The frequency of associated dental anomalies including agenesis, transposition and distoangulation was compared between patients with and without canine impaction at the CS. The measures were carried out with Dolphin Imaging software, version 10.5 (Dolphing Imaging, Charsworth, CA, USA). Comparisons of canine positional parameters between all three time points was performed using ANOVA. Comparisons of canine positional parameters between CS and NCS and between impaction and non-impaction cases were performed respectively using paired and independent ttests. Comparisons for the frequency of associated dental anomalies between impaction and non-impaction cases as well as the association between canine mesial displacement and impaction at the CS were assessed using Fisher test. The significance level regarded was 5%. Results: The prevalence of canine impaction at the CS was 24%. Canine positional parameters were statistically different between CS and NCS. Canines at the CS were usually more mesially angulated and more distant from the occlusal plane when compared to NCS. At the CS, canines that became impacted showed an increased angulation and height from the occlusal plane compared to canines with pontaneous eruption at all time points (T1, T2 and T3). An increased prevalence of lateral incisor agenesis at CS (72.2%) was observed in the subgroup with canine impaction compared to cases with canine spontaneous eruption (33.3%). No association between CS canine impaction and mesial displacement (zones) was found at any time point. Conclusions: Impacted canines at the CS in UCLP show an increased mesial angulation and an increased distance from the occlusal plane since the pre bone graft phase. The mesial displacement and superimposition with neighboring incisors should not be used as predictor factors for canine impaction in UCLP.